Spatio-temporal changes (1956-2013) of coastal ecosystems in Southern Iberian Peninsula (Spain) - Díez-Garretas, Blanca; Comino, Olga; Asensi, Alfredo (Mediterranean Botany, 2019)
Spatial and temporal changes of coastal vegetation since the 1950s along the southern Iberian Peninsula coast (Andalusia, Spain), have been analysed. Three examples have been selected: one on the Atlantic coast (Punta Umbria, Huelva) and two in the Mediterranean: Marbella (Malaga) and Punta Entinas-Sabinar (Almeria). The three areas are currently included in the Andalusian Network of Protected Natural Areas (RENPA). Aerial photographs dated in the years 1956-57 have been used and compared with the most recent (2013) using photointerpretation techniques and GIS (geographic information system) software. Observations have been completed with phytosociological data and historical cartography (forest and vegetation maps) that allowed us to analyse and identify the different communities and their transformation over 60 years. The results show the changes and impacts linked to the anthropic actions in this territory. In recent decades, the reforestation and expansion of urbanized areas are the main cause of coastal ecosystem alteration, especially affecting the Marbella coast that has had its dune system considerably reduced.
Keywords: Coastal vegetation; landscape transformation; aerial photographs; Mediterranean basin